-x^2+6x+-9=0

Simple and best practice solution for -x^2+6x+-9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x^2+6x+-9=0 equation:



-x^2+6x+-9=0
We add all the numbers together, and all the variables
-1x^2+6x=0
a = -1; b = 6; c = 0;
Δ = b2-4ac
Δ = 62-4·(-1)·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-6}{2*-1}=\frac{-12}{-2} =+6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+6}{2*-1}=\frac{0}{-2} =0 $

You can always share this solution

See similar equations:

| 2+21x+25x-2=138 | | x+152+x+40=168 | | 10x=17+13 | | 4n2+5n-250=0 | | (1.5+1.5)v=1.5(2.5)+1.5(-2.5) | | x+13=24/4x+13=24 | | .756=x/(x+10000) | | 6c+5/3=4c+1/2+5c/6 | | 1=0.25(2x+8) | | 3a+20=70 | | (4+9+16÷4)-8-3×5=z | | (4+9+16÷4)-8-3×5=s | | 55x+2=2*2-2x55 | | 3(x+1)=4(x+5) | | 6m+7=49* | | 3.8+4.5x-1.4=8.5 | | 0.25/3=x/11/3 | | -685+m/4=-11 | | 2x=40-12 | | 17x-6=7x-6 | | (X+4)+(3x-7)=(x-2)+(3x+8) | | 7x+x+8=56 | | x+2x+4x=?7x | | 7x^2+86x+399=0 | | (9?x)?(2?x)=7 | | 9?x?2?x=7 | | .3x+.5x(50-x)=18 | | 49x+2=0 | | -6x+-55=1 | | -6x+(-55)=1 | | -6x-20=70 | | 15x^2-46+16=0 |

Equations solver categories